Fish oil supplementation during pregnancy and allergic respiratory disease in the adult offspring - Hansen, Susanne; Strøm, Marin; Maslova, Ekaterina; Dahl, Ronald; Hoffmann, Hans Jürgen; Rytter, Dorte; Bech, Bodil Hammer; Henriksen, Tine Brink; Granström, Charlotta; Halldorsson, Thorhallur I.; Chavarro, Jorge E.; Linneberg, Allan; et al. (Journal of allergy and clinical immunology, 2017)
Maternal supplementation with long-chain n-3 polyunsaturated fatty acids can have immunologic effects on the developing fetus through several anti-inflammatory pathways. However, there is limited knowledge of the long-term programming effects. In a randomized controlled trial from 1990 with 24 years of follow-up, our aim was to determine whether supplementation with 2.7 g of long-chain n-3 polyunsaturated fatty acids in pregnancy can reduce the risk of asthma in offspring and allergic respiratory disease. The randomized controlled trial included 533 women who were randomly assigned to receive fish oil during the third trimester of pregnancy, olive oil, or no oil in the ratio 2:1:1. The offspring were followed in a mandatory national prescription register, with complete follow-up for prescriptions related to the treatment of asthma and allergic rhinitis as primary outcomes. Furthermore, the offspring were invited to complete a questionnaire (74% participated) and attend a clinical examination (47% participated) at age 18 to 19 years. In intention-to-treat analyses the probability of having had asthma medication prescribed was significantly reduced in the fish oil group compared with the olive oil group (hazard ratio, 0.54, 95% CI, 0.32-0.90; P = .02). The probability of having had allergic rhinitis medication prescribed was also reduced in the fish oil group compared with the olive oil group (hazard ratio, 0.70, 95% CI, 0.47-1.05; P = .09), but the difference was not statistically significant. Self-reported information collected at age 18 to 19 years supported these findings. No associations were detected with respect to lung function outcomes or allergic sensitization at 18 to 19 years of age. Maternal supplementation with fish oil might have prophylactic potential for long-term prevention of asthma in offspring.